Interaksi Sosial Siswa Reguler dengan Anak Berkebutuhan Khusus di Sekolah Dasar - Pindialesta, Kingkin; Isvandiana Purnamasari, Mega; Erviana, Lina (Scholarly Journal of Elementary School, 2025)
This study aims to determine the social interaction between regular students and children with disabilities and the efforts made by teachers in helping the social interaction process. This type of research is descriptive qualitative. The data collection techniques used observation, interviews and documentation. The results showed that: 1) Social interaction between regular students and children with disabilities at SD Negeri 2 Ketepung from the aspect of tolerance has been formed. Meanwhile, the cooperation aspect has not been fully formed. 2) Teachers' efforts to assist the social interaction process between regular students and children with disabilities in the learning process have been carried out. Teachers pay attention to the availability of learning tools and learning media used. However, in terms of learning methods, lectures dominate and teachers are still the center of the learning process (teacher center). So, the teacher's efforts in providing regular direction have helped to build tolerance, but the lack of appropriate learning methods has made cooperation, especially in group discussions, difficult.